Examination Of Digital Twin Applications In Industry 4.0 Based Production Systems And Predictive Maintenance Approaches - Aydın, Özgür; Akın, Erhan (Fırat University, 2021)
In this article, digital twin technology is discussed and focused on two areas: predictive maintenance and product and production optimizations in production processes. The study aims to present the latest developments in these two identified focal points and provide a guide for beginners. For this purpose, eighty eight studies in the literature published between 2015-2020 were systematically examined, analyzed and their results were examined. It has been observed that digital twins have entered a very rapid development process in the last two years, and they are preferred because of their benefits such as saving time, reducing maintenance and production costs and reducing production risks, as well as increasing productivity and quality.

Bu makalede dijital ikiz teknolojisinin ele alınmış olup, kestirimci bakım ve üretim süreçlerindeki ürün ve üretim optimizasyonları olmak üzere iki alana odaklanılmıştır. Çalışma, belirlenen bu iki odak noktadaki mevcut son gelişmeleri aktarmayı ve yeni başlayanlar için bir rehber sunmayı amaçlamaktadır. Bu amaç doğrultusunda literatürde yer alan ve 2015-2020 yılları arasında yayınlanan seksen sekiz çalışma sistematik olarak incelenmiş, analiz edilmiş ve sonuçları irdelenmiştir. Dijital ikizlerin son iki yılda çok hızlı bir gelişme süreci içerisine girdiği, özellikle zaman tasarrufu, bakım ve üretim maliyetlerinin azaltılması ve üretimdeki risklerin düşürülmesi bunların yanı sıra üretkenliğin ve kalitenin arttırılması gibi faydalarından dolayı tercih sebebi olduğu gözlenmiştir.
Endüstri 4.0 Tabanlı Üretim Sistemleri ve Kestirimci Bakım Yaklaşımlarında Digital İkiz Uygulamalarının İncelenmesi